Association of Genetic Variants Affecting microRNAs and Pancreatic Cancer Risk - Lu, Ye; Corradi, Chiara; Gentiluomo, Manuel; López de Maturana, Evangelina; Theodoropoulos, George E.; Roth, Susanne; Maiello, Evaristo; Morelli, Luca; Archibugi, Livia; Izbicki, Jakob R.; Sarlós, Patricia; Kiudelis, Vytautas; et al. (Frontiers in Genetics, 2021)
Genetic factors play an important role in the susceptibility to pancreatic cancer (PC). However, established loci explain a small proportion of genetic heritability for PC, therefore more progress is needed to find the missing ones. We aimed at identifying SNPs affecting PC risk through effects on micro-RNA (miRNA) function. We searched in silico the genome for SNPs in miRNA seed sequences or 3’UTR regions of miRNA target genes. Genome-wide association data of PC cases and controls from the Pancreatic Cancer Cohort (PanScan) Consortium and the Pancreatic Cancer Case-Control (PanC4) Consortium were re-analyzed for discovery, and genotyping data from two additional consortia (PanGenEU and PANDoRA) were used for replication, for a total of 14,062 cases and 11,261 controls. None of the SNPs reached genome-wide significance in the meta-analysis, but for three of them the associations were in the same direction in all the study populations and showed lower P-values in the meta-analyses than in the discovery phase. Specifically, rs7985480 was consistently associated with PC risk (OR=1.12, 95%CI 1.07-1.17, p=3.03x10-6 in the meta-analysis). This SNP is in linkage disequilibrium with rs2274048, which modulates binding of various miRNAs to the 3’UTR of UCHL3, a gene involved in PC progression. In conclusion, our results expand the knowledge of the genetic PC risk through miRNA-related SNPs and show the usefulness of functional prioritization to identify genetic polymorphisms associated with PC risk.